VEGF-A inhibits EphB4 and stimulates dll4 expression in adult endothelial cells - Yang, Chenzi (2013)
BACKGROUND: During vein graft adaptation to the arterial circulation, vascular endothelial growth factor (VEGF)-A expression transiently increases before becoming down-regulated; however the role of VEGF-A in venous remodeling is not clear. In addition, although VEGF-A stimulates angiogenesis and determines arterial identity in nascent arterial endothelial cells (EC), the role of VEGF-A in regulating identity in adult venous EC is also not clear. MATERIALS AND METHODS: EC, wild type (EphB4+/+) or heterozygous knockout (EphB4+/−), were stimulated with VEGF-A (0–100ng/ml) and examined with qPCR and Western blotting. RESULTS: VEGF-A (100ng/ml) inhibited expression of EphB4 and stimulated expression of dll4 but did not stimulate either notch or EphrinB2 expression in adult venous EC. Pretreatment with VEGFR2 neutralizing antibody abolished VEGF-stimulated down-regulation of EphB4 but not the up-regulation of Dll4. Pretreatment with PD98059 or wortmannin showed that VEGF-A down-regulation of EphB4 and up-regulation of dll4 are MEK-ERK-dependent but PI3k-Akt-independent. Compared to VEGF-induced EphB4 down-regulation and Dll4 up-regulation in control EC, reduced EphB4 signaling in EphB4+/− EC showed even further down-regulation of EphB4 and up-regulation of dll4. CONCLUSIONS: Despite the genetic programming of arterial and venous EC fate, VEGF-A can repress venous identity in adult venous EC without induction of arterial identity. These changes in adult EC in vitro recapitulate the changes in identity described during vein graft adaptation to the arterial environment in vivo.